PENGARUH MODEL PEMBELAJARAN TALKING STICK DENGAN METODE MATH MAGIC TERHADAP HASIL BELAJAR MATEMATIKA PADA POKOK BAHASAN KUBUS DAN BALOK DI KELAS V SD NEGERI 067849 MEDAN - Lailatun Nur Kamalia Siregar (State Islamic University of North Sumatra, 2019)
This study aims to determine the effect of significant between learning models talking stick method to the magic math mathematics learning outcomes in the classroom digunaakan V. This type of research is quantitative research with experimental methods of classic experimental design types (classical experimental design), which was held in Elementary School 067849 Medan. The population in this study consisted of all students in fifth grade elementary totaling 82 people, and also the whole population sample. The research instruments used were pretest and posttest. Statistical hypothesis testing formula used t-test, and the results of hypothesis test obtained by the average - average grade control = 67, average - average class experiment = 76, and t test with a value of t = 2.32> t table = 1.990. So we concluded that Ho is rejected and Ha accepted, which means there is significant influence between the learning model talking stick method on learning outcomes magic math mathematics on the subject of cubes and blocks class V SD Negeri 067849 Medan.